1985
DOI: 10.1093/cvr/19.7.442
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional in vivo pressure/diameter relationships in the canine main pulmonary artery

Abstract: Ultrasonic measurement of blood flow within the main pulmonary artery (MPA) requires a precise knowledge of the mean blood velocity within this vessel and the cross-sectional area (CSA). Small conformational changes in the elliptical shape of the MPA have substantial effects on the calculation of CSA and, subsequently, flow. We examined the extent of these changes by measuring the pulsatile and mean elliptical dimensions of the MPA in nine anaesthetised, open-chested, mechanically ventilated mongrel dogs using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The maximum dynamic compliance found by us (4.33 ± 2.19 mm 2 mmHg −1 ) was similar to the constant dynamic compliance of the pulmonary artery of dogs found by Patel et al (1960) (4.94 ± 1.85 mm 2 mmHg −1 ), but a twofold lower compliance of the dog pulmonary artery was found by Ingram et al (1970; 2.82 ± 1.15 mm 2 mmHg −1 ) and Johnson & Henry (1985; 2.25 mm 2 mmHg −1 ). In humans, a compliance of 10.04 ± 2.45 mm 2 mmHg −1 was found by Greenfield & Griggs (1963).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The maximum dynamic compliance found by us (4.33 ± 2.19 mm 2 mmHg −1 ) was similar to the constant dynamic compliance of the pulmonary artery of dogs found by Patel et al (1960) (4.94 ± 1.85 mm 2 mmHg −1 ), but a twofold lower compliance of the dog pulmonary artery was found by Ingram et al (1970; 2.82 ± 1.15 mm 2 mmHg −1 ) and Johnson & Henry (1985; 2.25 mm 2 mmHg −1 ). In humans, a compliance of 10.04 ± 2.45 mm 2 mmHg −1 was found by Greenfield & Griggs (1963).…”
Section: Discussionsupporting
confidence: 89%
“…This is only valid if creep is negligible and no influence of pressure and heart rate is present. Various authors have found that the creep of the pulmonary artery is indeed negligible (Patel et al 1960; Greenfield & Griggs, 1963; Ingram et al 1970; Shelton & Olson, 1972; Gozna et al 1974; Johnson & Henry, 1985). They have also found a constant dynamic compliance over a limited range of pulmonary arterial pressure.…”
mentioning
confidence: 99%
“…Advantages of an intraluminal probed over an extraluminal pulsed Doppler probe are the ability to fix the range and, thus, the sample volume size and the ability to obtain a profile across a true diameter rather than along an oblique axis, which may not be appropriate or optimal for curved or short vessels. Intraluminal diameters measured using the intraluminal probe have compared favorably with diameters measured with dimensional crystals in a previous study, 21 and color-flow Doppler imaging (Quantum Medical Systems, Issaquah, WA) have verified qualitatively the findings of die intraluminal technique in dogs and lambs. 414 Children with congenital heart disease often have altered pulmonary blood flow, with intracardiac shunting the most common etiology.…”
Section: Normalized Radial Distancementioning
confidence: 54%
“…A reliable measure requires assessment of the velocity profile (9,10), insonation angle (11) and accurate estimation of the cross-sectional area (CSA) (12). Of these parameters, estimation of CSA based on measurement of one diameter is considered to be the prime source of error (13,14).…”
mentioning
confidence: 99%
“…Of these parameters, estimation of CSA based on measurement of one diameter is considered to be the prime source of error (13,14). If the general assumption of a circular MPA is not valid (12,(15)(16)(17), different diameter measurements performed at the same cross-sectional level will obviously give different area estimates. This is important, for example, in assessing CO by means of pulsed Doppler echocardiography, since the MPA under closed chest conditions cannot be echocardiographically visualized in a crosssectional view even with the use of multiplane TEE (11).…”
mentioning
confidence: 99%